Nursing analysis and management of one case of fulminant fat embolism syndrome after open fractures of the tibia and fibula (1例开放性胫腓骨骨折后并发暴发型脂肪栓塞综合征的护理) - GE Daoqun (葛道群); BIAN Liyan (卞丽艳) (中西医结合护理)
To summarize the nursing analysis and experience of one patient with fulminant fat embolism syndrome (FES) after open fractures of the tibia and fibula. Fulminant FES after open fractures of the tibia and fibula is rare in clinical practice, with a short course, rapid progression and high mortality. It is required to take carefully observation of the condition, correction of shock at early stage, proper fixation of the affected limb and comprehensive treatment. (本文总结1例开放性胫腓骨骨折后合并发生暴发型脂肪栓塞综合征(FES)患者的护理分析及护理体会。开放性骨折发生暴发型FES临床较为罕见, 病程短、进展快、死亡率高。护理人员应仔细进行病情观察, 提高对疾病的识别能力, 早期纠正休克, 妥善固定患肢, 给予综合治疗, 最大程度挽救患者生命。)